2017
DOI: 10.1515/bjmg-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of FGFRs signaling pathway components in bladder cancer: A step toward personalized medicine

Abstract: Variations Improper activation and inappropriate expression of fibroblast growth factor receptors (FGFRs) in cancer suggests that they can act as therapeutic targets. Fibroblast growth factor receptor inhibitors are currently employed in clinical trials of different cancers. Regarding the essence and the importance of the personalized medicine, mainly mirrored by remarkable inter-individual variations in different populations, we aimed to perform a pilot study to address FGFR1 and FGFR3 expression levels and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…These findings underline the potential for FGFR3 as a marker for non-invasive, lower grade bladder tumors. The study also paralleled findings from other regional studies, such as Hammam et al [15] and Tavakkoly-Bazzaz J et al [16] , but unlike some studies, it found no significant correlation between FGFR3 gene amplification and tumor grade. The research, however, does affirm the significant correlation between FGFR3 expression and both tumor pathological stage and grade, suggesting a conserved pattern across different populations.…”
Section: Discussionsupporting
confidence: 88%
“…These findings underline the potential for FGFR3 as a marker for non-invasive, lower grade bladder tumors. The study also paralleled findings from other regional studies, such as Hammam et al [15] and Tavakkoly-Bazzaz J et al [16] , but unlike some studies, it found no significant correlation between FGFR3 gene amplification and tumor grade. The research, however, does affirm the significant correlation between FGFR3 expression and both tumor pathological stage and grade, suggesting a conserved pattern across different populations.…”
Section: Discussionsupporting
confidence: 88%
“…In an Iranian study, the authors found an increased expression of FGFR3 in most of the samples inall grades and stages (19).…”
Section: Discussionmentioning
confidence: 97%
“…The fibroblast growth factor receptor ( FGFR ) as a tyrosine kinase receptor is one of the main regulators of cell‐cycle progression, angiogenesis, and embryonic development. It has been reported that there were FGFR1 (OMIM: 136350) and FGFR3 (OMIM: 134934) overexpressions in low‐grade and all tumors, respectively, among a subpopulation of Iranian BC subjects (Ousati Ashtiani, Tavakkoly‐Bazzaz, et al, 2017). The small G‐protein signaling modulator 3 ( SGSM3 ) (OMIM: 610440) is a GTPase involving in regulation of G‐protein and Ras signaling (Yang, Sasaki, Minoshima, & Shimizu, 2007).…”
Section: Cell Signaling and Kinasesmentioning
confidence: 99%